Biological function identification of phage holin Hol-4086 and treatment of Staphylococcus aureus infection - Zheng, Chenyu; Di, Yaxin; Wang, Yingchun; Zhao, Huyang; Wang, Ruichong; Li, Guiwei; Wang, Xiaona; San, Zhifu; Jiang, Yanping; Cui, Wen; Li, Jiaxuan; Wang, Li; et al. (Frontiers in Microbiology, 2025)
The treatment of infections caused by drug-resistant Staphylococcus aureus has become increasingly difficult. In this study, the complete genome of phage 4086-1 against S. aureus was sequenced and shown to be 17,960 bp in size, with a GC content of 29.14%. Phylogenetic analysis demonstrated that phage 4086-1 exhibited a close relationship with the Staphylococcus phages SLPW, JPL-50, and LSA2366. BLAST analysis indicated that ORF12 of phage 4086-1 (termed Hol-4086) shares high identity with other reported phage-associated holins. Hol-4086 consists of 140 amino acids and exhibits high sequence identity with some members of the phage_holin_4_1 superfamily (18–125 amino acids). Hol-4086 was then expressed in Escherichia coli and detected using sodium dodecyl sulfate-polyacrylamide gel electrophoresis and western blotting. The results of a spot test demonstrated that Hol-4086 had substantial bacteriostatic effects on the host bacteria. S. aureus cells were exposed to Hol-4086 and observed using transmission electron microscopy and scanning electron microscopy. Bacterial cells treated with Hol-4086 showed ultrastructural and morphological changes. The detection of biofilm activity showed that Hol-4086 effectively inhibited and removed S. aureus biofilms. In vivo, treatment with Hol-4086 significantly reduced the number of bacteria, relieved inflammatory responses, and alleviated pathological changes in the organs of infected mice 48 h after treatment. These results demonstrate that Hol-4086 exhibits promising antibacterial potential as an alternative therapy for the treatment of infections caused by S. aureus.